Wawasan Al-Qur’an Tentang Respon Iblis Terhadap Perintah Sujud: Studi Pendekatan Teologis dan Sufistik - Muhtolib Muhtolib; Umar Fauzi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
Iblis is a creature of Allah SWT, who created from fire while Adam was created from the ground. His story is mentioned repeatedly in several surahs in the Qur’an. When Iblis was ordered by Allah SWT to prostrate to Adam, the Iblis was arrogant and considered himself better than Adam. So that Iblis becomes a group of infidels. This is expressed by Theological commentator based on QS. al-Baqarah [2]: 34. While according to Sufistic scholars, the Iblis is a creature of Allah SWT, who has ever had the most noble position and the highest monotheism towards Allah SWT. His reluctance to carry out Allah's command to prostrate to Adam is as proof that Iblis truly tawheed to Allah SWT and does not want to prostrate to other than Allah SWT.When rejecting the command to prostrate to Adam, Iblis considered the commandment of prostration as a form of test of monotheism. In the end, Allah SWT will forgive his sins and put them in heaven. The author tries to analyze these two problems by using the method of interpretation maudhu 'i, namely by collecting verses related to the story of Iblis in the Qur’an.